2016
DOI: 10.1017/s0007114516001549
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns in the French adult population: a study from the second French national cross-sectional dietary survey (INCA2) (2006–2007)

Abstract: Identification and characterisation of dietary patterns are needed to define public health policies to promote better food behaviours. The aim of this study was to identify the major dietary patterns in the French adult population and to determine their main demographic, socio-economic, nutritional and environmental characteristics. Dietary patterns were defined from food consumption data collected in the second French national cross-sectional dietary survey (2006–2007). Non-negative-matrix factorisation metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
50
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 86 publications
5
50
1
Order By: Relevance
“…According to the European Food Safety Authority (EFSA), heavy metals are considered as major chemical contaminants of the food chain [EFSA, 2014]. Data from previous studies based on the second French national cross-sectional dietary survey [ANSES, 2016] and the second French total diet study [ANSES, 2016] confirmed this conclusion, with the identification of many heavy metals in the French diet [Dubuisson et al, 2010;Gazan et al 2016;Traore et al, 2016]. The genotoxicity of these toxicants has been evaluated in different studies based on various genotoxic endpoints in different cell models.…”
Section: Discussionmentioning
confidence: 98%
“…According to the European Food Safety Authority (EFSA), heavy metals are considered as major chemical contaminants of the food chain [EFSA, 2014]. Data from previous studies based on the second French national cross-sectional dietary survey [ANSES, 2016] and the second French total diet study [ANSES, 2016] confirmed this conclusion, with the identification of many heavy metals in the French diet [Dubuisson et al, 2010;Gazan et al 2016;Traore et al, 2016]. The genotoxicity of these toxicants has been evaluated in different studies based on various genotoxic endpoints in different cell models.…”
Section: Discussionmentioning
confidence: 98%
“…Current research focuses on the study of dietary patterns, rather than analysis of given nutrients [14, 15]. Development of diet quality indices such as the EVIDENT diet index, represents a way to analyze FFQ data from a comprehensive viewpoint, using an approach different from the one most commonly applied to date.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to overcome the limitations of evaluating single nutrients and foods in isolation have led to a gradual shift in nutrition research to the evaluation of dietary patterns [1,2]. Although the investigation of dietary patterns is generally performed in terms of the daily intake of individual foods or food groups [3][4][5][6], an increasing number of studies have focused on dietary intake at the level of each eating occasion (i.e., breakfast, lunch, dinner, and snack) or meal patterns [7][8][9]. Studying dietary patterns at this level rather than overall dietary patterns might be more relevant considering synergies and interactions during digestion and metabolism [10].…”
Section: Introductionmentioning
confidence: 99%